2010
DOI: 10.1508/cytologia.75.319
|View full text |Cite
|
Sign up to set email alerts
|

Sex Chromosome Evolution Revealed by Physical Mapping of SlAP3X/Y in the Dioecious Plant Silene latifolia

Abstract: Summary Sex-linked genetic markers of Silene latifolia were mapped to the sex chromosomes with the aim of analyzing their evolutionary origins. SlAP3X/Y has been particularly uncertain for years. Its X-counterpart has not been identified, and very few Y-deletion mutants delete SlAP3Y. In this study, we verified the sex chromosome-linkage of SlAP3X and SlAP3Y through cloning, sequencing, and fluorescent in situ hybridization (FISH). SlAP3X, spanning a region of 1.6 kb, consists of 6 exons and 5 introns. SlAP3Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
0
9
1
Order By: Relevance
“…4a,b ). The difference from previous FISH mapping, which concluded that it was located near the centromere 41 , is that, unlike the probe used here, the probe region used previously contained repetitive sequences, as revealed by sequencing BAC clones containing SlAP3Y and SlAP3 X 42 .…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…4a,b ). The difference from previous FISH mapping, which concluded that it was located near the centromere 41 , is that, unlike the probe used here, the probe region used previously contained repetitive sequences, as revealed by sequencing BAC clones containing SlAP3Y and SlAP3 X 42 .…”
Section: Resultscontrasting
confidence: 60%
“…Their corresponding Y-copies were mapped by DelMapper in this study. FISH signals of SlAP3X/Y are indicated by green circles; the genetic location of SlAP3X is derived from Ishii et al 41 PAR; pseudo autosomal region.…”
Section: Figurementioning
confidence: 99%
“…The approach of testing known flower development genes has been largely superseded by high-throughput sequencing methods. Searches have found MADs-box and ABC(DE) genes involved in flower whorl development on the sex chromosomes of S. latifolia and Asparagus officinalis (Matsunaga et al, 2003;Park et al, 2003;Cegan et al, 2010;Nishiyama et al, 2010;Penny et al, 2011). However, genes that control floral organ identity are not generally promising candidates.…”
Section: Plant Sex-determining Locimentioning
confidence: 99%
“…Silene is the best studied of genera with heteromorphic chromosomes and although its Y chromosome harbors numerous intact genes, some with Xlinked counterparts, few of these genes are observed to have floral development function (Matsunaga, 2006). Among those genes found on the Y chromosome and known to be involved in flower development are an APETALLA 3 ortholog (Matsunaga et al, 2003;Nishiyama et al, 2010), two SEPALLATA orthologs (Matsunaga et al, 2004), and two WUSCHEL orthologs (Kazama et al, 2012). However, it is not clear if any of these genes function in a sexually deterministic fashion.…”
Section: Introductionmentioning
confidence: 99%